2014
DOI: 10.1038/srep05622
|View full text |Cite
|
Sign up to set email alerts
|

High energy density rechargeable magnesium battery using earth-abundant and non-toxic elements

Abstract: Rechargeable magnesium batteries are poised to be viable candidates for large-scale energy storage devices in smart grid communities and electric vehicles. However, the energy density of previously proposed rechargeable magnesium batteries is low, limited mainly by the cathode materials. Here, we present new design approaches for the cathode in order to realize a high-energy-density rechargeable magnesium battery system. Ion-exchanged MgFeSiO4 demonstrates a high reversible capacity exceeding 300 mAh·g−1 at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
216
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(226 citation statements)
references
References 33 publications
10
216
0
Order By: Relevance
“…Without ILs, the G3 solution of Mg(Tf 2 N) 2 shows as large current density as IL/G2 or IL/G4 mixture. 18,19 Moreover, the IL/G3 sample kept in a glove box for 7 days after mixing changed to yellowish from colorless while the others remained fairly colorless (see Fig. 8).…”
Section: Bath Properties-mentioning
confidence: 98%
See 1 more Smart Citation
“…Without ILs, the G3 solution of Mg(Tf 2 N) 2 shows as large current density as IL/G2 or IL/G4 mixture. 18,19 Moreover, the IL/G3 sample kept in a glove box for 7 days after mixing changed to yellowish from colorless while the others remained fairly colorless (see Fig. 8).…”
Section: Bath Properties-mentioning
confidence: 98%
“…[16][17][18][19] We have also reported an amide-containing glyme-IL solution with which room temperature electrodeposition of Mg metal was successfully demonstrated. In these Mg 2+ -amide-containing glyme solutions, however, sizable amounts of free glyme molecules exists, as in IL-free glyme electrolytes, and thus all the reported electrolytes are either volatile and/or have limited anodic stability to some extent.…”
mentioning
confidence: 94%
“…Recently, however, it was reported that the reversible Mg plating and stripping was achieved with Mg(N(CF 3 SO 2 ) 2 ) 2 (Mg(TFSA) 2 ) dissolved in triethyleneglycol dimethyl ether (triglyme) based solutions. 8,9 Since the electrolyte solution shows the high ionic conductivity of 10 ¹3 S cm ¹1 at room temperature and relatively high oxidation stability, the glyme based solutions will be the new standard for the Mg secondary batteries' electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…However, new energy source with higher capacity and better rate performance is required because LIBs are not good enough for larger and higher power machines such as electric vehicles. Recently, metal-air, [11][12][13][14] lithium-sulfur (LIS), [15][16][17][18][19][20] sodium-ion [21][22][23][24][25] batteries and others [26][27][28][29] have been attracting much attention as post-LIB energy devices.…”
Section: Introductionmentioning
confidence: 99%